Challenges of Making Processed Food - Case Study of the Instant Rice Industry CV Mitra Berkah - Paulus Sukapto; Marihot Nainggolan (Ann Publisher, 2026)
Background. The instant rice industry in Indonesia faces various challenges, ranging from lower competitive prices to organoleptic quality and food safety issues. This study examines these challenges through a case study of CV Mitra Berkah, an instant rice producer in Bandung. Through mentoring that focuses on the Standard Operating Procedures (SOPs) of the Occupational Safety and Health Management System (SMK3), food hygiene, and digital marketing strategies. Aims. This study aims to identify challenges, evaluate the effectiveness of interventions, analyze the impact of marketing, and provide recommendations. Methods. The research methodology combines qualitative and quantitative approaches using observation, interviews, and document analysis. Result. The results show an increase in awareness of K3 and hygiene, product quality assurance, and a 60% increase in sales turnover in six months through digital marketing. Conclusion. This study confirms the importance of integrating sound production practices and adaptive marketing strategies to sustain MSMEs in the processed-food industry.